A Rare Case of Cardiac Recovery after Acute Myocarditis from West Nile Virus Infection: A Review of the Current Literature - KaChon Lei; Wilbur Ji; Bhavana Bhaya; Chowdhury Ahsan (Case Reports in Cardiology)
West Nile Virus (WNV) myocarditis is nearly fatal, according to the current medical literature. We report a previously healthy 37-year-old Caucasian male who presented to our facility with two days of progressive lower extremity weakness, fever, edema, and shortness of breath found to have left ventricular global hypokinesis with an ejection fraction of less than 25%, consistent with acute viral myocarditis. He also has concomitant WNV meningoencephalitis due to his altered mentation. He was found to have a positive serum WNV IgM suggestive of a diagnosis of WNV myocarditis. He was intubated and was placed on vasoactive pressors for supportive care due to evidence of mixed cardiogenic and septic shock. After two weeks of hemodynamic support, we discovered a near-complete cardiac recovery, as shown on a repeat transthoracic echocardiography (TTE) and a normalized mean arterial blood pressure. This is a unique case report because near fatality is often associated with WNV myocarditis secondary to tachyarrhythmia, and there are currently no documented cases that are suggestive of cardiac recovery from the current literature.